2003
DOI: 10.1007/s00417-003-0803-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of chorioretinal atrophy around choroidal neovascularization in pathologic myopia

Abstract: The factors influencing the development of chorioretinal atrophy differ according to patient age. Local factors, such as CNV size, determine the tendency to develop chorioretinal atrophy in young patients. Systemic factors, such as patient age, play a greater part in older subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…Kojima et al followed the natural history of mCNVs in older patients, and reported that eyes with larger CNVs were associated with the development of a ChRA [4]. In our study, the patient's age at the onset was not significantly associated with an enlargement of the ChRA.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Kojima et al followed the natural history of mCNVs in older patients, and reported that eyes with larger CNVs were associated with the development of a ChRA [4]. In our study, the patient's age at the onset was not significantly associated with an enlargement of the ChRA.…”
Section: Discussioncontrasting
confidence: 71%
“…They also reported the relationship between the regression pattern of CNV after IVB and the development ChRA [3]. Kojima and associates reported the factors influencing the development of ChRA in non-treated eyes [4].…”
Section: Introductionmentioning
confidence: 96%
“…Fatores locais, como o tamanho da membrana neovascular de coróide, determinam atrofia em jovens. Fatores sistêmicos, como a idade, têm importância maior em idosos (10) . Em relação ao estafiloma posterior, Steidl e Pruett notaram que pacientes com estafilomas de menor profundidade apresentavam uma maior freqüência de membranas neovasculares de coróide, hemorragias e pior acuidade visual, sugerindo que o desenvolvimento de membranas neovasculares de coróide requer uma preservação relativa dos coriocapilares (11) .…”
Section: Discussionunclassified
“…Previous studies have identified the following factors as significantly associated with a poor visual outcome: development of chorioretinal atrophy, large baseline CNV, older age, subfoveal location of the CNV, poor baseline BCVA, regression patterns of the CNV, subretinal hemorrhage, and previous PDT [12,[15][16][17][18][19]21] . Similar to previous studies, we identified older age, longer duration of myopic CNV, poor baseline BCVA, and large baseline CNV as prognostic factors for a poor final visual outcome.…”
Section: Discussionmentioning
confidence: 99%